Refurbishing Recent Emerging Technology Trends in Construction Industry - Mahajan, Gayatri (Techniques and Innovation in Engineering Research Vol. 6, 2022)
Adoption of recent digital transformation technology is required today to speed up business and serves as the foundation for construction improvement. Incorporating and practicing of the technologies such as cloud-based communication and collaboration solution, BIM, Construction Management (CM) Software, AR/ VR, 3D printing, Digital Twins, AI, Big Data, IoT, Blockchain, Modular Construction, Offsite Manufacturing, Prefabrication, Robotic, Drones, Mobile Apps and 5G expedite the progress in Construction Industry (CI). The objective of this article is to provide the rising pattern amongst digital technology trends in construction which are identified based on a study carried out during 2020-2022. Result reveals that number of construction technology trends vary from 4 to 20 for CI, and eventually reaches to 27 for Civil Engineering (CE). Adoption and implementation of these technology trends increases efficiency and productivity, reduces risks and time, provides higher security and green sustainability, and improves the overall economics. The challenges and solutions are highly embracing in the field of construction. Thus, the CI is constantly evolving with introductory of new technologies and these innovative technologies show potential in reshaping construction industry operations and provides guidelines for future projects.